PERENCANAAN STRUKTUR RUMAH SUSUN SEDERHANA SEWA UNGARAN MENGGUNAKAN BETON PRACETAK - Syarifuddin Syarifuddin; Anjar Satria Nugraha; Parang Sabdono; Rudi Yuniarto Adi (Jurnal Karya Teknik Sipil, 2016)
Ungaran Low Cost Apartment located at Karimunjawa street, Gedanganak, West Ungaran. This Low Cost Apartment consist of 5 level floors designed using precast concrete systems. The Building is designed with a Special Moment Resisting Frames (SMRF) for it structure system. This building design based on procedure for calculation of concrete structure for building (SNI 03-2487-2002), Earthquake resilience planning procedures for non structural building and building (SNI 1726-2012), and value of earthquake parameter response was download from Ministry of Public Work’s website. In order to easier building structure analysis, design of Ungaran low cost apartment are helped by SAP.2000 version 14 and PCA COL program.Choosing the precast method is important thing, because one of the weakness of the precast system is on connection between it’s elements. Ungaran low cost apartment designed using Adhi BCS (Beam Coloumn Slab) system. Characteristic of Adhi BCS system is additional concrete topping above plate and beam that adding rigidity it’s structure.